The Latvian Unit Named After Leons Paegle in the Spanish Civil War (1936–1939) - Ginta Ieva Bikše (Latvijas Universitātes Žurnāls. Vēsture, 2025)
The unit named after Leons Paegle was one of the largest Latvian units formed within the International Brigades. However, its composition remained unclear even after recollections of some of the unit’s members were published during the Soviet occupation. The aim of the article is to analyse the composition of the unit named after Paegle and its characteristics, focusing on its motivation for being in Spain. The battle experience of its members has been described only briefly. Most of the unit members had communistic beliefs and saw their time in Spain as useful for political purposes of the party, however, their experience relating the Spanish Civil War was not uniform and the unit had difficulties to keep up morale, leading to a high percentage of deserters.